Prevalence of malaria and its risk factors in Lake Tana and surrounding areas, northwest Ethiopia - Fasil Adugna; Melaku Wale; Endalkachew Nibret (Malaria Journal, 2022)
Abstract Background In Ethiopia, malaria is a major concern to the health, and socio-economic development of the country because of its occurrence at the peak agricultural activities. Factors such as environmental, human host, parasite, and vector determine malaria transmission. Therefore, the present study was conducted to determine the prevalence and associated factors of malaria among febrile patients who visited selected health centres. Methods Institutional-based cross-sectional study was conducted between October 2020 to July 2021 in eight selected health centres located in Lake Tana and its surrounding areas. A simple random sampling technique was used to select febrile patients. Thick and thin blood films were prepared and processed according to the WHO guidelines. Socio-demographic and malaria risk factors were collected from study participants who could read and write using a self-administered questionnaire, whereas face-to-face interview was used to collect information from those participants who could not write and read. The strength of association between risk factors and malaria was assessed using univariate and multivariate logistic regression models. Results Of the total (531) febrile patients, 75.3% were malaria negative and 24.7% (overall prevalence) were malaria confirmed cases. Most of the infections were caused by Plasmodium falciparum (72.5%) followed by Plasmodium vivax (23.7%) and mixed-species (3.8%). The highest prevalence was recorded in Kidist Hana (51.5%) followed by Robit (34.8%), Gorgora (30.3%), and Wusha Tiris (25%) health centres. In terms of months, the highest prevalence (37.5%) was detected in October whereas the lowest (14%) was in March. Logistic regression analysis revealed that gender (p = 0.023), educational level (p = 0.025), study month (p = 0.036), presence of eave in the house (p = 0.002) and wall openings (p = 0.041), not using bed nets (p = 0.001), sleeping in the same house with cattle (p = 0.031) and the distance between mosquito-breeding site and living house (p ...